Red Lake Breccia: Arts-Integration to Map a Fractured Relationship with Geoscientific Knowledge Production Networks - Johnstone, Sandra (Art/Research International, 2022)
Through this work I engaged the geological process of brecciation as a metaphor in an arts-integrated critical analysis of an event that changed the trajectory of my career and initiated the transformation of my relationship with geoscientific knowledge and professional practice. I integrated personal stories from my time as an exploration geologist in Red Lake, ON, and reflections on my current role as a post-secondary geoscience educator, to specifically situate myself within this inquiry. I used mixed-media acrylic painting to analyze information and experiences across sometimes dissonant paradigms. Though common in educational research, arts-integrated practices are still extremely rare for research focused on post-secondary technoscientific training. This work provides an opportunity to think differently. It is a first step toward making visible, and challenging, some of the hidden lessons and omissions in geoscience education that have insulated geoscientists from the effects of their knowledge production.